Pengembangan Lembar Kerja Peserta Didik Terintegrasi Nilai Islam dengan Model Quantum Learning di Sekolah Dasar - Dahlianti, Revi; Faisal Ahmad (Milenial: Journal for Teachers and Learning, 2025)
This study aims to produce Islamic-based student worksheets withmodelsstudent quantum learninglearning outcomes. to improvethe learning outcomes of students in grade IV Elementary School (SD) are valid and practical. This type of research is research and development (R&D) with the ADDIE model. This study used random sampling, namely for small group trials, a sample of 9 students was taken at SDN 020 Balung. The data collection technique is a LKPD validation questionnaire consisting of material experts, and education technology experts. Practicality questionnaire filled by students and teachers. The results of the assessment of the validity of the LKPD by the technology validator obtained an average of 85% with the criteria of "very valid" and the results of the assessment of the validity of the LKPD by the material validator obtained an average of 87% with the criteria of "very valid". The practicality of assessing student responses is 93% in the "very practical" category and the teacher's response is 92% in the "very practical" category. It can be concluded that the Islamic-based LKPD with themodel is quantum learning very valid and very practical so it is suitable for use by fourth grade students of Elementary School on theme 8 (My Living Area) sub-theme 1 (My Living Environment) is suitable for use by fourth grade students Elementary School